SOCIO-PSYCHOLOGICAL ASPECTS OF SBLING RELATIONSHIPS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Each child's ability to find his place in society, to have a certain position, directly depends on interpersonal relations in the family. The system of family relationships also includes relationships with brothers and sisters, i.e. siblings. These relationships are long-term and significant for a person, and they are complex and two-way in nature. On the one hand, siblings are close relatives who form a separate system in the family. They are united by parents, similar living conditions and upbringing, common family values and traditions, daily communication, and a large number of emotional and practical connections. On the other hand, a sibling relationship is a unique relationship that a child has with other children. Its peculiarity is that the child cannot control whether or not he has a sibling, the gender of the sibling, or the attitude of his parents towards him. [4-236] This can cause ambivalent experiences in him because of his smallness. That is, the child may want to be with his sibling, but at the same time, he may dream of being the only one for his parents.